The International, Epistemic Fallacy and Possibilities of Critical Realism - Ulman, Burak; Balta-Paker, Evren; Agcan, Muhammed A. (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2011)
This article examines the main assumptions of neo-realism and neo-liberalism from the perspective of a critical realist philosophy of science. Although neo-realist and neo-liberal theories of international relations (IR) disagree on some issues, they do have a common ontological understanding of the international based heavily on the principle of anarchy. The centrality of and emphasis on anarchy, in turn, creates a monolithic, unhistorical and asocial idea of the international. This article argues that a critical realist philosophy of science, as proposed by Roy Bhaskar, provides a good framework to pursue the ontological interrogation required to deconstruct the anarchy centered idea of the international assumed by rationalist/positivist theories. Critical realism allows us to identify the crucial error that the rationalist/positivist tradition commits: which is to fall into the trap of 'epistemic fallacy', where ontological questions concerning the nature of being are posed and answered in epistemological terms. Critical realism not only provides a tool to investigate the ontological assumptions of mainstream IR theories but also to propose a differentiated and stratified ontology that can open the door to the mutual recognition of alternative perspectives.
Keywords: Theories of International Relations; Positivism; Ontology; Critical Realist Philosophy of Science; Roy Bhaskar; SCIENTIFIC REALISM; LIBERAL LEGACIES; KANT; International Relations